PENGARUH KONVERSI BANK KONVENSIONAL MENJADI BANK SYARIAH TERHADAP RISIKO KEBANGKRUTAN STUDI KASUS PADA BANK ACEH - Setiadi, Taufan Prasojo Wicaksono; Al Kautsar1, Sinathrya; Indra, Lusiana; Hanggraeni, Dewi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
Based on Law No. 21 of 2008 concerning Sharia banking, the 2-window banking principle in Indonesia will expire at the maximum in year 2023 where banks that have been running Sharia businesses using Sharia Business Units (UUS) will be forced to spin off or convert into commercial banks of Sharia. This study was conducted to predict bankruptcy at bank Aceh after conversion from conventional banks to Islamic banks in 2014-2018 using Z-Score method. The analysis technique in this study is using financial ratio ROA with the formula Z-Score = (ROA + E / A) / S.D ROA. This study concludes that H1 can be accepted because the Syariah after conversion shows that the change in risk level in sharia is better than when it was still a conventional Aceh bank.